Job Satisfaction among Secondary-School-Heads: A Gender Based-Comparative Study - Qaiser Suleman; Ishtiaq Hussain (MDPI AG, 2018)
The purpose of the study was to examine and compare the job satisfaction of male and female secondary-school heads in Khyber Pakhtunkhwa, Pakistan. All the male and female secondary-school heads working in pubic secondary schools of Khyber Pakhtunkhwa constituted the population of the study. A total sample of 402 secondary-school heads was selected through multistage sampling technique in which 260 were males and 142 were females. Descriptive and quantitative research design was used. A standardized tool (i.e., "Minnesota Satisfaction Questionnaire" (MSQ)) was used for data collection. For statistical analysis, proper descriptive statistics (i.e., mean and standard deviation) and inferential statistics (i.e., independent samples t-test) were employed. The findings revealed that secondary-school heads were found dissatisfied with ability utilization, advancement, education policies and practices, creativity, compensation, supervision (HR), supervision (technical), and working conditions. There was no significant difference between the job satisfaction of male and female secondary-school heads with respect to overall intrinsic as well as extrinsic factors. Based on these findings, it was recommended that productive and effective measures should to be taken by the Ministry of Education Khyber Pakhtunkhwa to maintain and strengthen the employees' level of satisfaction at each level. The Ministry of Education should devise compelling, productive, and effective education policies that are promising to the employees' prosperity and organizational productivity.